The void in finance - Amin Samman (Finance and Society, 2023)
There is no proper place within economic thought for the void. It appears nowhere in the canonical texts of political economy, let alone the discourse of conventional economics. Yet one cannot shake the sense that it is implied in most if not all financial commentary. At the very least, the void exerts a magnetic pull on a range of related terms in the lexicon. Could it be that through these it grounds the financial imagination in fundamental ways?
Keywords: 300; finance; financial nihilism; Hyman Minsky; Jean Baudrillard; Money; void